Improved robot-assisted laparoscopic telesurgery: feasibility of network converged communication. Issue 11 (16th September 2021) - Chu, G; Yang, X; Luo, L; Feng, W; Jiao, W; Zhang, X; Wang, Y; Yang, Z; Wang, B; Li, J; Niu, H
Abstract : The converged transmission-assisted network communication architecture used in this study could meet the requirements of telesurgery, and effectively guarantee the security and immediacy of communication. With the security, flexibility, and universality of the network converged transmission, the clinical practical application of telesurgery and telemedicine would step up to a higher level.